2021
DOI: 10.1007/s10666-021-09750-0
|View full text |Cite
|
Sign up to set email alerts
|

Economic Complexity and Environmental Performance: Evidence from a World Sample

Abstract: In this paper, we analyze the relationship between economic complexity and environmental performance using annual data on 88 developed and developing countries for the period of 2002–2012. We use the Economic Complexity Index, which links a country’s productive structure with the amount of knowledge and know-how embodied in the goods it produces, and the Environmental Performance Index as a measure of environmental performance. We show that moving to higher levels of economic complexity leads to better overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
54
2
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(93 citation statements)
references
References 128 publications
9
54
2
5
Order By: Relevance
“…The literature review demonstrated that the economic complexity index aims to decrease pollution emissions and improve the quality of the environment (e.g., Dogan et al [6], Chu [7], Romero and Gramkow [8], and Boleti et al [9]).…”
Section: Introductionmentioning
confidence: 99%
“…The literature review demonstrated that the economic complexity index aims to decrease pollution emissions and improve the quality of the environment (e.g., Dogan et al [6], Chu [7], Romero and Gramkow [8], and Boleti et al [9]).…”
Section: Introductionmentioning
confidence: 99%
“…Neagu (2019) nd that the Environmental Kuznet Curve hypothesis is valid for both whole sample of 25 European Union countries and six country members (Belgium, France, Italy, Finland, Sweden, and the United Kingdom). Other authors, such as Boleti et al (2021), Chu (2021), Dogan et al (2019), and Romero and Gramkow (2021) extend to a larger sample. Boleti et al (2021) nd that higher level of ECI leads to better overall environmental performance (which is constituted from three aspects, namely health impacts, air quality, and water and sanitation) but induces air polluted in a sample of 88 developed and developing countries.…”
Section: Brief Literature Reviewmentioning
confidence: 91%
“…Other authors, such as Boleti et al (2021), Chu (2021), Dogan et al (2019), and Romero and Gramkow (2021) extend to a larger sample. Boleti et al (2021) nd that higher level of ECI leads to better overall environmental performance (which is constituted from three aspects, namely health impacts, air quality, and water and sanitation) but induces air polluted in a sample of 88 developed and developing countries. Dogan et al (2019) nd that impact of ECI on carbon dioxide emissions varies according to the economic development of a country.…”
Section: Brief Literature Reviewmentioning
confidence: 91%
“…An often suggested means of achieving global export competitiveness is the expansion of the production and export of value-added goods, which can be achieved through improvements in economic complexity (Erkan & Yildirimci, 2015;Hidalgo & Hausmann, 2009). Economic complexity represents the productive knowledge and diversity of a particular country (Boleti et al, 2021;Hausmann et al, 2014). Conceptually, economic complexity highlights the ability of countries to produce locally based knowledge goods and to substantially diversify their export baskets.…”
Section: Introductionmentioning
confidence: 99%
“…Economic complexity represents the productive knowledge and diversity of a particular country (Boleti et al, 2021; Hausmann et al, 2014). Conceptually, economic complexity highlights the ability of countries to produce locally based knowledge goods and to substantially diversify their export baskets.…”
Section: Introductionmentioning
confidence: 99%